2013
DOI: 10.2196/jmir.2682
|View full text |Cite
|
Sign up to set email alerts
|

Social and Self-Reflective Use of a Web-Based Personally Controlled Health Management System

Abstract: BackgroundPersonally controlled health management systems (PCHMSs) contain a bundle of features to help patients and consumers manage their health. However, it is unclear how consumers actually use a PCHMS in their everyday settings.ObjectiveTo conduct an empirical analysis of how consumers used the social (forum and poll) and self-reflective (diary and personal health record [PHR]) features of a Web-based PCHMS designed to support their physical and emotional well-being.MethodsA single-group pre/post-test onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 54 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…Previously, we have demonstrated that these PCHMS features have broad utility in a number of health areas including in vitro fertilization and influenza vaccination [42,43]. The current study extends those applications to help-seeking behaviors for physical and emotional well-being.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Previously, we have demonstrated that these PCHMS features have broad utility in a number of health areas including in vitro fertilization and influenza vaccination [42,43]. The current study extends those applications to help-seeking behaviors for physical and emotional well-being.…”
Section: Discussionmentioning
confidence: 57%
“…Healthy.me was iteratively developed, and its first version was tested in other settings such as in vitro fertilization and influenza vaccination [42,43]. The first version contained features such as journey, the personal health record, and online appointment booking with the university primary care service.…”
Section: Methodsmentioning
confidence: 99%
“…It has been designed and validated in a two-group, parallel, randomised controlled trial as effective in increasing consumers' vaccination rates. 33 34 The app has been tailored to promote effective self-management of gout and long-term adherence to ULT. The app was developed, using dimensions of the Health Belief Model: perceived susceptibility, perceived severity, perceived benefits and perceived barriers.…”
Section: Open Accessmentioning
confidence: 99%
“…Online social networks seem to be an effective mean to influence health‐related behaviors for consumers and patients . Some diseases such as obesity, depression, or diabetes proved to be sensitive to social media and social network interventions . With the spread of consumer digital devices, online social media are expected to play an increasing role in the prevention and management of diseases .…”
Section: Introductionmentioning
confidence: 99%